Analisis Pola Asuh Orang Tua Terhadap Perilaku Keagamaan Peserta Didik - Nurul Muslim, Muhammad Zamzam; Azizah, Salma Nur; CS, Nurhamzah (Prodi PAI IAILM Suryalaya, 2024)
This study aims to determine the effect of parenting style on the religious behavior of students at Sukaratu Public Elementary School. Parenting is a pattern, attitude, treatment, style, model, or way parents establish relationships with their children. The method used in this study is a descriptive method through a quantitative approach, namely research that seeks to reveal current conditions/conditions by processing the numbers obtained from the research results. Based on the results of the research and data processing, it was found that the upbringing of parents at SDN Sukaratu was classified as good with an average count (X ) ̅=54.95. when confirmed on the interpretation scale, it is in the Good classification (Interval 52.08 – 56.62). While the Religious Behavior of Students at SDN Sukaratu produces an average count (X ) ̅ = 61.39. When confirmed on the interpretation scale, it is a sufficient classification (Interval 56.68 – 63.37). And the effect of parenting style on the religious behavior of students at SDN Sukaratu has a significant positive effect, as evidenced by the results of research and calculations with a Spearman rank of 0.68 which is in the High Correlation Classification (0.61 – 0.80 interval) ). Apart from that, from the calculation results t_(count) and t_(table) it turns out that t_(count) = 4.9708 t_(table) 1.45. So, by comparing the two figures it is evident that t_(count )=4.9708 ≥ t_(table )1.45. So, the relationship between variable X (Parent Parenting) and variable Y (Religious Behavior of Learners) is 45.79%. This shows that the religious behavior of students is influenced by parenting patterns of 45.79%. So that 54.21% of students' religious behavior is determined by factors outside the research. both internal factors and external factors such as the influence of the family environment, community, school, and social environment or peers.